Evaluating the Production Efficiency of Smallholder Dairy Farms in Vietnam: A Case Study in Can Tho City - Phuong, Quang Nguyen (Research on World Agricultural Economy, 2026)
This study investigates the production efficiency of smallholder dairy farmers in Dai Tam commune, Can Tho City, Vietnam, with the aim of identifying the key factors that influence productivity and sustainability. To achieve this objective, the research applies a combination of Data Envelopment Analysis (DEA) and Tobit regression models. The DEA approach is used to measure both Technical Efficiency (TE) and Scale Efficiency (SE), while the Tobit model is employed to examine the socio-economic determinants affecting production performance. The results show that the average technical efficiency of dairy farmers under constant returns to scale and variable returns to scale is 0.732 and 0.904, respectively. These findings suggest that milk output could be improved by approximately 26–27% through more efficient use of existing inputs, without requiring an expansion in herd size. The Tobit regression results further indicate that farming experience, participation in cooperatives, technical training, and access to credit have significant positive effects on production efficiency. Although the overall performance of the surveyed farmers is relatively stable, production efficiency remains constrained by uneven adoption of technology, limited capital resources, and the use of substandard breeds. Based on these findings, the study recommends strengthening technical training programs, promoting cooperative linkages, improving farmers’ access to financial resources, and enhancing farm management practices. These measures are expected to contribute to higher productivity and support the sustainable development of the dairy sector in the Mekong Delta. ER